|
HPT $\Leftrightarrow \begin{cases}(x^3-3x^2+3x-1)-12(x-1)=(y^3+3y^2+3y+1)-12(y+1) \\ y-2=\sqrt{x-3} \end{cases}$ $\Leftrightarrow \begin{cases}(x-1)^3-12(x-1)=(y+1)^3-12(y+1) \qquad (1)\\ y-2=\sqrt{x-3}\qquad (2)\\x\ge 3, y \ge 2 \end{cases}$ Đặt $f(t)=t^3-12t \quad t \ge 2$. Có $f'(t)=3t^2-12 \ge 0 \quad \forall t \ge 2$ suy ra $f$ là hàm đồng biến với $t \ge 2.$ Từ PT $(1)\Leftrightarrow f(x-1)=f(y+1)\Leftrightarrow x-1=y+1\Leftrightarrow x-4=y-2$ Thay điều này vào $(2)$ ta được $x-4=\sqrt{x-3}\Leftrightarrow \begin{cases}x \ge 4 \\ (x-4)^2=x-3 \end{cases}\Leftrightarrow x=\dfrac{1}{2}\left (9+\sqrt 5 \right )$ Vậy $x=\dfrac{1}{2}\left (9+\sqrt 5 \right ), y =\dfrac{1}{2}\left (5+\sqrt 5 \right )$.
|